Intrafirm Competition and Charter Evolution in the Multibusiness Firm - Birkinshaw, Julian (Institutional Knowledge at Singapore Management University, 2010)
We develop a theoretical framework for a specific form of intrafirm competition, namely the extent of overlap between the charters of two or more units in a single organization. This phenomenon is commonly seen in large organizations, e.g., cases of two business units producing competing products, or two product development groups trying to solve the same technological problem, but the existing academic literature produces little insight into the forms intrafirm competition takes, or the conditions under which it is beneficial or harmful to the organization. Building on the concept of an organizational charter (Galunic and Eisenhardt 2001), we identify forms of intrafirm competition: the dynamic community model has fluid and frequently changing charter boundaries, and it emerges through the creation of strategic options in the face of a changing environment; the coexistence model has fixed and relatively static charter boundaries, and it owes its existence to economies of scope and differentiation of unit charters to cover multiple market segments. In the body of the paper we develop a theoretical framework to specify the environmental and organizational conditions under which each form of intrafirm competition is expected to occur. [PUBLICATION ABSTRACT]